Preparation and Evaluation of Chitosan-Eudragit L 100 Polymer-based Sustained Release Tablet of Diclofenac Sodium - J. Wadher, Dr. Kamlesh (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: The objective of this investigation is to develop a sustained release matrix tablet by taking a mixture of chitosan (CS) and Eudragit L100 polymers and then to study the drug release pattern for a low solubility drug of diclofenac sodium (DS). Materials and Methods: The short biological half-life and frequent dosing make DS an ideal candidate for sustained release dosage forms. The tablets were prepared by direct compression method. All the batches were evaluated for thickness, weight variation, hardness, and drug content uniformity and in vitro drug release. Results: Fourier-transform infrared spectroscopy study was conducted to study any interaction between dug and ingredients. Hydrophilic matrix of CS alone could not control the diclofenac release effectively for 12 h whereas when combined with Eudragit L100 could slow down the release of drug and can be successfully employed for: formulating sustained-release matrix tablets. Conclusion: Fitting the data to Korsmeyer equation indicated that diffusion along with erosion could be the mechanism of drug release.